(untitled) (Journal of Educational Sciences, 2021)
The theoretical research is devoted to a number of main problems, which are the lack of an indi- vidual, differentiated approach to the person choosing a profession, the lack of qualified personnel, poor monitoring of the modern labor market. The main content of the proposed modules in the article: “Computer as a means of information processing” considers the safety practices and rules of operation on a computer, computer devices, software, and operating system. Applied course of teaching elements of higher mathematics to future teachers of mathematics “formation of students’ own logical thought and mathematical culture by increasing the level of applied courses of teaching elements of higher mathematics, the formation of students ‘ skills to solve complex non-standard problems, increasing the interest of students of the natural-mathematical direction. “Fundamentals of Entrepreneurship” allows students to get acquainted with the main theoretical aspects of doing business, acquire initial practical skills to create their own business and subsequently use the acquired knowledge and skills to develop business plans, project solutions in the study of professional disciplines. This article shows the current problems of using the methods of the course “Kasipkerlik negizderi” for future teachers of mathematics, the importance of psychological readiness of students to choose a further profession, as well as a more in-depth expansion of the horizons of professions and areas of their activities. Key words: teacher, student, mathematics, technology, methods, educational process, computer, entrepreneurship, professional choice, individual characteristics.